KINERJA GURU PENDIDIKAN AGAMA ISLAM DALAM PEMBELAJARAN PADA SMAN 1 PELAIHARI - Hidayatul Jannah & Muhamad Ramli (Al-Falah: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2017)
This study aims to determine the performance of Islamic Religious Education teachers at SMAN 1 Pelaihari Lesson Year 2014/2015. With the problems formulated in this study is how the performance of Islamic Religious Education teachers and what factors affect the performance of teachers of Islamic Education in learning at SMAN 1 Pelaihari Lesson Year 2014/2015. Based on the formulation of the problem, this study aims to find out how the performance of Islamic Religious Education teachers and what factors affect the performance of Islamic Religious Education teachers in learning at SMAN 1 Pelaihari Lesson Year 2014/2015. Subjects in this study are 3 teachers of Islamic Religious Education, while the object is the performance of Islamic Religious Education teachers and the factors that influence it. Data collection efforts in the field were conducted using observation, interview, and documentary techniques. Data processing techniques through editing, data classification and interpretation of data. Then the data analysis is done by taking the conclusion. Based on the research results, it can be concluded that the performance of Islamic Religious Education teachers in learning at SMAN 1 Pelaihari good and satisfactory. Seen from the performance of teachers make learning program planning, implementing the learning process and carry out an evaluation (assessment) is achieved well. While the factors that influence the educational background of teachers PAI 2 people including a graduate degree, while one of them is still in the process of completion bachelor, and teaching experience over 1 year even one of them reaching 30 years, and the environment is very supportive on the performance of teachers Education Islam. Keywords: Performance, Islamic Education Teachers, Learning.